Roles of the ClpX IGF loops in ClpP association, dissociation, and protein degradation - Amor, Alvaro J. (Protein Sci, 2019)
IGF‐motif loops project from the hexameric ring of ClpX and are required for docking with the self‐compartmentalized ClpP peptidase, which consists of heptameric rings stacked back‐to‐back. Here, we show that ATP or ATPγS support assembly by changing the conformation of the ClpX ring, bringing the IGF loops closer to each other and allowing efficient multivalent contacts with docking clefts on ClpP. In single‐chain ClpX pseudohexamers, deletion of one or two IGF loops modestly slows association with ClpP but strongly accelerates dissociation of ClpXP complexes. We probe how changes in the sequence and length of the IGF loops affect ClpX–ClpP interactions and show that deletion of one or two IGF loops slows ATP‐dependent proteolysis by ClpXP. We also find that ClpXP degradation is less processive when two IGF loops are deleted.